Hubungan Motivasi dan Manajerial Kepala Sekolah dengan Kinerja Guru SD Gugus I Kecamatan Sibulue Kabupaten Bone - A. Silviana Sirajuddin; Arismunandar; Muhammad Irfan (Jurnal Pustaka Cendekia Pendidikan, 2025)
The aim of this research is to determine 1) the description of the principal's motivation and managerial performance and the performance of teachers at SD Cluster I, Sibulue District, Bone Regency, 2) the relationship between principal motivation and the performance of elementary school teachers at cluster I, Sibulue District, Bone Regency. 3) the managerial relationship between the principal and Performance of Gugus I Elementary School Teachers, Sibulue District, Bone Regency 4) The relationship between motivation and managerialism of the school principal together on the performance of Gugus I Elementary School teachers, Sibulue District, Bone Regency. This research uses quantitative research methods. The research was carried out at Gugus I Elementary School, Sibulue District, Bone Regency. The independent variables in this research are the principal's motivation and managerial skills, while the dependent variable is teacher performance. The population in this study were all teachers in elementary school cluster I, Sibulue District, totaling 100 people, while the sample was 30 people. Research data was obtained by distributing questionnaires. The data analysis technique is multiple regression analysis technique. Based on the results of the research, it shows that there is a relationship between the motivation and managerialism of school principals and the performance of elementary school teachers in Cluster I, Sibulue District, Bone Regency.